"Meriah: Mari Sikat Gigi Untuk Senyum Yang Cerah" As An Effort To Improve Children's Tooth Brushing Skills - Aprilia Yuanita Anwaristi; Alfiana Nur Faizah; Salsabilla Putri Zahradini (Journal of Community Capacity Empowerment, 2025)
This dental and oral screening activity is part of our efforts to increase students' awareness and knowledge about the importance of maintaining dental and oral health from an early age. In addition, this activity aims to identify dental and oral health problems that students may face, as well as provide appropriate education so that they can maintain better dental and oral hygiene. This report contains a series of activities, screening results, and recommendations for follow-up actions that can be taken to improve dental and oral health among students of Al-Azhar Syifa Budi Surakarta Elementary School. Based on the def-t index category, it shows that the prevalence of caries is quite high. There are several factors that influence the screening results, including: 1. Oral care habits in children.. 2. The level of understanding of parents and children about the importance of dental and oral health has a direct impact on children's oral hygiene habits. 3. Children's fear or anxiety about dental examinations can affect cooperation during screening. 4. The accuracy of the tools and the expertise of medical personnel in conducting screening affect the accuracy of the results. We hope that with this activity, students can be more concerned and responsible for their dental and oral health. We also express our gratitude to all parties who have supported the implementation of this activity, both from the school, health workers, and all participants who have actively participated in this activity.